2005
DOI: 10.1530/rep.1.00454
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fluidity and the ability of domestic bird spermatozoa to survive cryopreservation

Abstract: The ability to survive cryopreservation varies in spermatozoa from different bird species. Among the biological factors potentially responsible for such differences, species variations in membrane fluidity have a role in the restoration of the physiological state after freezing. Membrane fluidity may be assessed by measuring fluorescence polarization anisotropy with a fluorescent dye. Anistropy values are proportional to membrane rigidity and consequently inversely proportional to membrane fluidity. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
61
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(85 citation statements)
references
References 26 publications
10
61
0
14
Order By: Relevance
“…pid ratio did not differ between fresh and cryopreserved chicken sperm (Blesbois et al, 2005). Together with these data, our results suggest that in addition to sterols, phospholipids might also be lost from membranes in chicken sperm after cryopreservation.…”
Section: Discussionsupporting
confidence: 68%
“…pid ratio did not differ between fresh and cryopreserved chicken sperm (Blesbois et al, 2005). Together with these data, our results suggest that in addition to sterols, phospholipids might also be lost from membranes in chicken sperm after cryopreservation.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have demonstrated large differences in the membrane composition of avian spermatozoa, including cholesterol content and the membrane phospholipids 34. The cholesterol proportion of rooster sperm cells is lower than that in the Guinea fowl and could reflect the differences in sperm membrane fluidity 35. As found for mammals, this could influence sperm morphology in these avian species.…”
Section: Discussionmentioning
confidence: 92%
“…Because of this cholesterol influence on plasma membrane properties, many studies have explored the hypothesis of a cholesterol-induced stabilization of spermatozoa with regard to cryopreservation. In descriptive studies, it was surmised that species with the highest cholesterol content had the most cryoresistant spermatozoa (mammals [15]; fish [16]), although this hypothesis was challenged in poultry species [17]. Interindividual comparisons of spermatozoa within the same species also led to contradictory interpretations on the role of cholesterol: a positive relation between plasma membrane cholesterol content and cryoresistance was observed in goats [18], while an inverse relation was shown in fowl [19], rainbow trout [20], and stallions [18].…”
Section: Introductionmentioning
confidence: 99%